2012
DOI: 10.1002/term.1565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infrapatellar and subcutaneous adipose tissue stromal vascular fraction and stromal/stem cells in osteoarthritic subjects

Abstract: Since inflammatory mechanisms have been postulated to link obesity to osteoarthritis, the current study evaluated the ratio of immune cells to multipotent stromal cells within the infrapatellar fat pad (IPFP) and subcutaneous adipose tissue (SQ) of the knee; each depot has potential as a source of regenerative cells. The immunophenotypes of stromal vascular fraction (SVF) and adipose‐derived stem cells (ASCs) of the IPFP and SQ were determined in tissues from osteoarthritic subjects (n = 7) undergoing total kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
2
22
2
Order By: Relevance
“…Adipose-derived stem cells (ASCs) have been successfully used in several in vivo studies for cartilage generation (14)(15)(16). Thus, when developing treatments for knee chondral lesions, infrapatellar fat pad and knee subcutaneous adipose tissue, that are easily accessible during orthopaedic surgery, can be considered appealing sources for MSCs harvesting (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) have been successfully used in several in vivo studies for cartilage generation (14)(15)(16). Thus, when developing treatments for knee chondral lesions, infrapatellar fat pad and knee subcutaneous adipose tissue, that are easily accessible during orthopaedic surgery, can be considered appealing sources for MSCs harvesting (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…5). Interestingly, AAT-ASCs and ScAT-ASCs from osteoarthritis (OA) subjects were reported to exhibit similar osteogenic potential [18]. Reassuming, it seems that ASCs derived from rheumatoid articular adipose tissue have stronger differentiation potential despite localization in the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Omental ASC were expanded to P1 before their immunophenotype was analyzed. The detailed protocols used for flow cytometry testing have been published in our previous articles [Yu et al, 2010;Carvalho et al, 2011;Pires de Carvalho et al, 2014].…”
Section: Immunophenotypementioning
confidence: 99%
“…While the majority of tissue engineering studies using human stromal/stem cells have employed subcutaneous ASC , direct comparison of infrapatellar-and subcutaneous-derived ASC from individual donors found that the two populations did not display significant differences based on differentiation or immunophenotype; the only exception was the endothelial cell-associated antigen, CD31, which was more abundant in subcutaneous ASC [Pires de Carvalho et al, 2014]. Likewise, comparisons between ASC derived from Bichat's or the buccal fat pad and subcutaneous adipose depots of human subjects or pigs have determined that both ASC populations exhibit similarities based on the immunophenotype as well as adipogenic and osteogenic differentiation abilities [Farre-Guasch et al, 2010;Niada et al, 2013;Kishimoto et al, 2014].…”
Section: Pe Igg1mentioning
confidence: 99%
See 1 more Smart Citation